Entropy and creation cold dark matter models. Issue 1 (28th March 2019) - Valentim, R.; Jesus, J. F.
Abstract : Entropy is a fundamental concept from thermodynamics, and it can be used to study models in the context of the creation cold dark matter. A general feature of these models is that thermodynamic equilibrium is reached at last at the de Sitter era. Total Universe's entropy is calculated based on three terms: apparent horizon ( S h ), entropy of matter ( S m ), and entropy of radiation ( S γ ). The constraints from total entropy come from the first and second derivatives ( S ′ ≥ 0 and S ″ < 0) to estimate the parameters of the model with the general matter creation rate. The preliminary outcomes suggest limits for these parameters.